Carbetocin at Elective Cesarean Delivery. Issue 3 (September 2015) - Khan, M.; Balki, M.; Ahmed, I.; Farine, D.; Seaward, G.; Carvalho, J.C.A.
<x xml:space="preserve">Abstract</x> (Can J Anesth. 2014;61:242–248)